Painting robot with three axis motion - Renggi Yunatatak; Jajang Jaenudin; Luqman Hakim; Mustaza Ma’a (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Paint was applied directly to the painted surface while painting with a brush. There are occasionally unsatisfactory outcomes, such as paint stacking or streaks remaining. Spray guns yield better paint results, therefore a robot was developed that can regulate the spray gun's movement in order to apply paint. A painting robot that resembles an arm is one that has three axes of movement. The robot can move left-right on the x axis, up-down on the y axis, and back-front on the z axis. Its end effector is a spray cannon. An ultrasonic sensor is used to measure the distance between components and the spray gun; when the sensor measures near distances, such as between 4 and 8 cm, the test sensor distance measurements have a larger average error. When the test reading distance is increased from 10 cm to 14 cm, the average error reduces. Superior painting outcomes can be achieved with a paint distance of 10 cm, an air pressure of 80 psi, and a spray gun arm movement speed of 25 rpm. With average x-axis movement of 74.6 cm, y-axis movement of 14.8 cm, and z-axis movement of 88.2 cm, the largest volume that can be painted is 97,517.5 cm3. The rotation of the arm is used to determine the angular rotation needed to paint components. Painting the left side of the component at an angle of 10°, the back side at an angle of 100°, the right side at an angle of 190°, and only painting the front side of the component at the required angle of 90° require the rotational movement of the arm to the left.